Answer:
C
Step-by-step explanation:
The correct answer would be
. Therefore, none of the answer choices fulfill this and A and B are not correct.
Answer:
Step-by-step explanation:
-0.25
-1/3
1/4
0.3
Answer:
t3 = 8, t5 = 14
Step-by-step explanation:
t3 = 2 + (3-1) × 3
t3 = 2 + (2) × 3
t3 = 2 + 6
t3 = 8
t5 = 2 + (5-1) × 3
t5 = 2 + (4) × 3
t5 = 2 + 12
t5 = 14
Y = 3x + 3 this is equation 1
y = x -1 this is equation 2
since equation 1 and 2 already defined y in terms of x, we're just gonna substitute y into the other equation. as 2 is shorter I'm going with that today
x - 1 = 3x +3
-1 - 3 = 3x - x
-4 = 2x
x = -2
now we've got x just sub it in equation 2
y = -2 -1
y = -3
so the answer is (-2,-3)
Im not sure why it brought me here it just brought me here sorry